Flexible emotional regulation typology: associations with PTSD symptomology and trait resilience - Eric Spikol; Emily McGlinchey; Martin Robinson; Cherie Armour (BMC Psychology, 2024)
Abstract Background Multiple factors influence posttraumatic stress disorder (PTSD) risk in trauma exposed individuals. An established association exists between trait resilience and decreased PTSD distress and between emotion regulation (ER) ability/flexibility and trait resilience. Typologies in ER ability/flexibility, associated with trait resilience and PTSD experience, could explain the difference in risk. This study aimed to explore the relationship between ER ability, ER flexibility, context sensitivity, resilience, and PTSD. Methods Data from N = 563 trauma exposed UK residents was used in a latent profile analysis (LPA) and membership in the resultant profiles was explored in a logistic regression of sociodemographics, resilience, and PTSD symptomology. Results Analysis showed 2 latent profiles (High Flexibility, Low Flexibility) typified by emotion regulation ability and context sensitivity. Members of the Low Flexibility profile were more likely to be younger, male, endorsing less trait resilience, and experiencing negative cognition/mood and hyperarousal PTSD symptomology. Conclusions Difficulties in ER ability and flexibility could be improved with targeted learning in a therapeutic or home setting, potentially increasing trait resilience after trauma exposure and reducing PTSD distress.